Landscapes and Geomorphology : A Very Short Introduction - Goudie, Andrew; Viles, Heather (Oxford Oxford University Press, 2010)
Landscapes are all around us, but most of us know very little about how they have developed, what goes on in them, and how they react to changing climates, tectonics, and human activities. This Very Short Introduction discusses the key ideas and methods used to study and examine landscapes, and their importance in cultural terms.
Include Index.
A Very Short Introduction.
Keywords: Geomorphology